Enhanced Expression of Janus Kinase–Signal Transducer and Activator of Transcription Pathway Members in Human Diabetic Nephropathy - Berthier, Celine C.; Zhang, Hongyu; Schin, MaryLee; Henger, Anna; Nelson, Robert G.; Yee, Berne; Boucherot, Anissa; Neusser, Matthias A.; Cohen, Clemens D.; Carter-Su, Christin; Argetsinger, Lawrence S.; Rastaldi, Maria P.; et al. (Diabetes (New York, N.Y.), 2009)
Enhanced Expression of Janus Kinase–Signal Transducer and Activator of Transcription Pathway Members in Human Diabetic Nephropathy Celine C. Berthier 1 , Hongyu Zhang 1 , MaryLee Schin 1 , Anna Henger 1 , Robert G. Nelson 2 , Berne Yee 3 , Anissa Boucherot 1 , Matthias A. Neusser 1 5 , Clemens D. Cohen 4 5 , Christin Carter-Su 6 , Lawrence S. Argetsinger 6 , Maria P. Rastaldi 7 , Frank C. Brosius 1 and Matthias Kretzler 1 1 Department of Internal Medicine-Nephrology, University of Michigan, Ann Arbor, Michigan 2 Department of Epidemiology and Clinical Research Branch, National Institute of Diabetes and Digestive and Kidney Diseases, Phoenix, Arizona 3 Southwest Kidney Institute, Phoenix, Arizona 4 Clinic for Nephrology, University Hospital, Zurich, Switzerland 5 Department of Physiology, University of Zurich, Zurich, Switzerland 6 Department of Molecular and Integrative Physiology, University of Michigan, Ann Arbor, Michigan 7 Renal Research Laboratory, Fondazione D'Amico per la Ricerca sulle Malattie Renali and Fondazione IRCCS Policlinico, Milan, Italy Corresponding author: Frank C. Brosius III, fbrosiusatumich.edu Abstract OBJECTIVE— Glomerular mesangial expansion and podocyte loss are important early features of diabetic nephropathy, whereas tubulointerstitial injury and fibrosis are critical for progression of diabetic nephropathy to kidney failure. Therefore, we analyzed the expression of genes in glomeruli and tubulointerstitium in kidney biopsies from diabetic nephropathy patients to identify pathways that may be activated in humans but not in murine models of diabetic nephropathy that fail to progress to glomerulosclerosis, tubulointerstitial fibrosis, and kidney failure. RESEARCH DESIGN AND METHODS— Kidney biopsies were obtained from 74 patients (control subjects, early and progressive type 2 diabetic nephropathy). Glomerular and tubulointerstitial mRNAs were microarrayed, followed by bioinformatics analyses. Gene expression changes were confirmed by real-time RT-PCR and immunohistological staining. Samples from db/db C57BLKS and streptozotocin-induced DBA/2J mice, commonly studied murine models of diabetic nephropathy, were analyzed. RESULTS— In human glomeruli and tubulointerstitial samples, the Janus kinase (Jak)-signal transducer and activator of transcription (Stat) pathway was highly and significantly regulated. Jak-1, -2, and -3 as well as Stat-1 and -3 were expressed at higher levels in patients with diabetic nephropathy than in control subjects. The estimated glomerular filtration rate significantly correlated with tubulointerstitial Jak-1, -2, and -3 and Stat-1 expression ( R 2 = 0.30–0.44). Immunohistochemistry found strong Jak-2 staining in glomerular and tubulointerstitial compartments in diabetic nephropathy compared with control subjects. In contrast, there was little or no increase in expression of Jak/Stat genes in the db/db C57BLKS or diabetic DBA/2J mice. CONCLUSIONS— These data suggest a direct relationship between tubulointerstitial Jak/Stat expression and progression of kidney failure in patients with type 2 diabetic nephropathy and distinguish progressive human diabetic nephropathy from nonprogressive murine diabetic nephropathy. Footnotes Published ahead of print at http://diabetes.diabetesjournals.org on 18 November 2008. A.B. is currently affiliated with sanofi-aventis Deutschland, Frankfurt, Germany. The content of this article is solely the responsibility of the authors and does not necessarily represent the official views of the National Institute of Diabetes and Digestive and Kidney Diseases or the National Institutes of Health. Readers may use this article as long as the work is properly cited, the use is educational and not for profit, and the work is not altered. See http://creativecommons.org/licenses/by-nc-nd/3.0/ for details. The costs of publication of this article were defrayed in part by the payment of page charges. This article must therefore be hereby marked “advertisement” in accordance with 18 U.S.C. Section 1734 solely to indicate this fact. Accepted November 12, 2008. Received September 28, 2008. DIABETES